966 Free of choice options to reduce sitting: does it work?. (24th April 2018) - Hermans, V; De Swerdt, S; Seghers, J; Godderis, L; Daenen, L
Abstract : Introduction: Increased cardiovascular diseases, obesity and diabetes are sedentary lifestyle. To tackle this problem, strategies to reduce sitting such as sit-stand tables. very low quality of evidence for the interventions. This study impact of a intervention reduc sitting Methods: An RCT-study was conducted in the office environment of a pharmaceutical company.: presentation of importance of good ergonomics/movement at the office and a check of the ergonomic set-up of the workstation. the experimental group (19) could use sit-stand tables, desk bikes and sit-stand chairs for 4 weeks. lso a weekly motivation email was sent. Sitting time was measured using ActivPAL TM accelerometers before and after the 4 weeks intervention both groups. Data were analysed using SPSS. Results significant decrease in sitting time was the experimental group The reduction in sitting time was of the subjects attributed the reduction in sitting time to the use of sit-stand tables. of the desk bikes and sit-stand supports was. Half of the subjects revealed that these devices were no important contributors to reduced sitting. Conclusion: A decreased sitting time in the intervention group, subjectively mainly attributed to the use of sis important factors. this further.